Early event status informs subsequent outcome in newly diagnosed follicular lymphoma. Issue 11 (3rd September 2016) - Maurer, Matthew J.; Bachy, Emmanuel; Ghesquières, Hervé; Ansell, Stephen M.; Nowakowski, Grzegorz S.; Thompson, Carrie A.; Inwards, David J.; Allmer, Cristine; Chassagne‐Clément, Catherine; Nicolas‐Virelizier, Emmanuelle; Sebban, Catherine; Lebras, Laure; et al.
Abstract : Recent advances in follicular lymphoma (FL) have resulted in prolongation of overall survival (OS). Here we assessed if early events as defined by event‐free survival (EFS) at 12 and 24 months from diagnosis (EFS12/EFS24) can inform subsequent OS in FL. 920 newly diagnosed grade 1‐3A FL patients enrolled on the University of Iowa/Mayo Clinic Lymphoma SPORE Molecular Epidemiology Resource (MER) from 2002‐2012 were initially evaluated. EFS was defined as time from diagnosis to progression, relapse, re‐treatment, or death due to any cause. OS was compared to age‐and‐sex‐matched survival in the general US population using standardized mortality ratios (SMR) and 95% confidence intervals (CI). We used a cohort of 412 FL patients from two Lyon, France hospital registries for independent replication. Patients who failed to achieve EFS12 had poor subsequent OS (MER SMR = 3.72, 95%CI: 2.78‐4.88; Lyon SMR = 8.74, 95%CI: 5.41‐13.36). Conversely, patients achieving EFS12 had no added mortality beyond the background population (MER SMR = 0.73, 95%CI: 0.56‐0.94, Lyon SMR = 1.02, 95%CI: 0.58‐1.65). Patients with early events after immunochemotherapy had especially poor outcomes (EFS12 failure: MER SMR = 17.63, 95%CI:11.97‐25.02, Lyon SMR = 19.10, 95%CI:9.86‐33.36; EFS24 failure: MER SMR = 13.02, 95%CI:9.31‐17.74, Lyon SMR = 7.22, 95%CI:4.13‐11.74). In a combined dataset of all patients from both cohorts, baseline FLIPI was no longer informative in EFS12 achievers. Reassessment of patient status at 12 months from diagnosis in follicular lymphoma patients, or at 24 months in patients treated with immunochemotherapy, is a strong predictor of subsequent overall survival in FL. Early event status provides a simple, clinically relevant endpoint for studies assessing outcome in FL. Am. J. Hematol. 91:1096–1101, 2016. © 2016 Wiley Periodicals, Inc.